The cyclic GMP‐AMP synthetase–STING signaling pathway is required for both the innate immune response against HBV and the suppression of HBV assembly. (9th November 2015) - Dansako, Hiromichi; Ueda, Youki; Okumura, Nobuaki; Satoh, Shinya; Sugiyama, Masaya; Mizokami, Masashi; Ikeda, Masanori; Kato, Nobuyuki
Abstract : During viral replication, the innate immune response is induced through the recognition of viral replication intermediates by host factor(s). One of these host factors, cyclic GMP‐AMP synthetase (cGAS), was recently reported to be involved in the recognition of viral DNA derived from DNA viruses. However, it is uncertain whether cGAS is involved in the recognition of hepatitis B virus (HBV), which is a hepatotropic DNA virus. In the present study, we demonstrated that HBV genome‐derived double‐stranded DNA induced the innate immune response through cGAS and its adaptor protein, stimulator of interferon genes (STING), in human hepatoma Li23 cells expressing high levels of cGAS. In addition, we demonstrated that HBV infection induced ISG56 through the cGAS–STING signaling pathway. This signaling pathway also showed an antiviral response towards HBV through the suppression of viral assembly. From these results, we conclude that the cGAS–STING signaling pathway is required for not only the innate immune response against HBV but also the suppression of HBV assembly. The cGAS–STING signaling pathway may thus be a novel target for anti‐HBV strategies. Abstract : We demonstrated that HBV genome‐derived dsDNA and HBV infection induced the innate immune response through the cGAS‐STING signaling pathway in human hepatoma Li23 cells expressing high level of cGAS. This signaling pathway showed an antiviral response against HBV through the suppression of viral assembly. Our data provide a novel target for anti‐HBV strategies.